A network analysis based proteomic and transcriptomic investigation into HIV-Tat induced neuronal dysfunction and the neuroprotective effect of lithium - Ganief, Tariq Ahmad (Division of Medical Biochemistry, 2017)
HIV-associated neurocognitive disorders (HAND) affect up to 70% of HIV positive individuals and are the leading cause of dementia in patients under 40 years. Despite this, the molecular mechanisms involved in the onset of HAND are not well understood. Among a number of plausible etiological agents of HAND, HIV-Tat has been shown to be neurotoxic in vitro and in vivo, but the basis of its induced neuronal dysregulation remains relatively poorly characterised, giving rise to various competing theories. This thesis describes differential, quantitative proteomic analyses of HIV-Tat-treated neuronal cells in vitro, the goal being to gain deeper insight into the underlying molecular basis of this HIV-Tat-mediated dysregulation, as well as to potentially inform better patient treatments in the future. To achieve this goal, deep, quantitative proteomic analysis of HIV-Tat treated SILAC-labelled SH-SY5Y neuroblastoma cells was carried out, alongside transcriptomic analysis of the same system in which 3077 proteins were identified and quantified with 407 proteins and 1074 genes being differentially expressed. Subsequently, label-free proteomics analysis was used to study the ability of lithium - a proposed new treatment for HAND - to suppress the HIV-Tat induced dysregulated molecular phenotype in SH-SY5Y cells in which 3757 were identified and quantified with 360 and 531 being significantly differentially expressed in HIV-Tat and HIV-Tat + lithium treated cells, respectively.